Effects of Alkalinization and Rehydration on Plasma Potassium Concentrations in Neonatal Calves with Diarrhea - Trefz, F.M. (J Vet Intern Med, 2015)
BACKGROUND: Increased plasma potassium concentrations (K(+)) in neonatal calves with diarrhea are associated with acidemia and severe clinical dehydration and are therefore usually corrected by intravenous administration of fluids containing sodium bicarbonate. OBJECTIVES: To identify clinical and laboratory variables that are associated with changes of plasma K(+) during the course of treatment and to document the plasma potassium‐lowering effect of hypertonic (8.4%) sodium bicarbonate solutions. ANIMALS: Seventy‐one neonatal diarrheic calves. METHODS: Prospective cohort study. Calves were treated according to a clinical protocol using an oral electrolyte solution and commercially available packages of 8.4% sodium bicarbonate (250–750 mmol), 0.9% saline (5–10 L), and 40% dextrose (0.5 L) infusion solutions. RESULTS: Infusions with 8.4% sodium bicarbonate solutions in an amount of 250–750 mmol had an immediate and sustained plasma potassium‐lowering effect. One hour after the end of such infusions or the start of a sodium bicarbonate containing constant drip infusion, changes of plasma K(+) were most closely correlated to changes of venous blood pH, plasma sodium concentrations and plasma volume (r = −0.73, −0.57, −0.53; P < .001). Changes of plasma K(+) during the subsequent 23 hours were associated with changes of venous blood pH, clinical hydration status (enophthalmos) and serum creatinine concentrations (r = −0.71, 0.63, 0.62; P < .001). CONCLUSIONS AND CLINICAL IMPORTANCE: This study emphasizes the importance of alkalinization and the correction of dehydration in the treatment of hyperkalemia in neonatal calves with diarrhea.